Furosemide in Hypovolemic shock - Khaleel, Khalid Ali (AL-Kindy College Medical Journal, 2020)
Background: Shock is a common clinical state, we face chocked patients in causality, surgical and gynecological  specialties like stab wounds, road traffic accidents, placenta preavia, placenta accrete, placenta pericreta, ectopic pregnancy, perforated viscus  etc. All such patients undergo surgical exploration and majority of them are shifted to ICU to complete monitoring and support. High percent of them they develop acute kidney injury intra and postoperatively and carry high mortality rate because of not so good nursing care in ICU in Iraq.Objective: to clarify that Furosemide can protect kidney function during shock and reduce ICU admission and mortality rate.Method: 100 shocked patient were enrolled in this study which was done in medical city hospital,  Al-Sadder General hospital and Alkindi teaching hospital in Iraq/Baghdad from January 2019 to June 2020. Patients were divided into 2 groups: group SN this include 50 patient who received 2 ml normal saline as placebo(control group)and second group SL which include 50 patient who received 2 ml (20 mg) furosemide (study group). This trial was double blind study, both the patient and the junior anesthesia doctor do not know about the study conducted. patients below age of 14 years were excluded from the study. 98 patients of those 100 patients were involved in multiple stab wound injury, multiple bullet injury and road traffic accident and only 2 patients were diagnosed as ectopic pregnancy.Result: ICU admission and mortality rate was less in patients receiving furosemide compared to patients received placebo (2% and 14% versus 1%and 7%respectively).Conclusion: furosemide reduces ICU admission and mortality rate in shocked patients.